Dopant-Site Determination in Y- and Sc-Doped (Ba0.5Sr0.5)(Co0.8Fe0.2)O3−δ by Atom Location by Channeling Enhanced Microanalysis and the Role of Dopant Site on Secondary Phase Formation. (22nd December 2015) - Meffert, Matthias; Störmer, Heike; Gerthsen, Dagmar
Abstract: (Ba0.5 Sr0.5 )(Co0.8 Fe0.2 )O3− δ (BSCF) is a promising material with mixed ionic and electronic conductivity which is considered for oxygen separation membranes. Selective improvement of material properties, e.g. oxygen diffusivity or suppression of secondary phase formation, can be achieved by B-site doping. This study is concerned with the formation of Co-oxide precipitates in undoped BSCF at typical homogenization temperatures of 1, 000°C, which act as undesirable nucleation sites for other secondary phases in the application-relevant temperature range. Y-doping successfully suppresses Co-oxide formation, whereas only minor improvements are achieved by Sc-doping. To understand the reason for the different behavior of Y and Sc, the lattice sites of dopant cations in BSCF were experimentally determined in this work. Energy-dispersive X-ray spectroscopy in a transmission electron microscope was applied to locate dopant sites exploiting the atom location by channeling enhanced microanalysis technique. It is shown that Sc exclusively occupies B-cation sites, whereas Y is detected on A- and B-cation sites in Y-doped BSCF, although solely B-site doping was intended. A model is presented for the suppression of Co-oxide formation in Y-doped BSCF based on Y double-site occupancy.